Bacteria-responsive intelligent wound dressing: Simultaneous In situ detection and inhibition of bacterial infection for accelerated wound healing. (April 2018) - Zhou, Jin; Yao, Danyu; Qian, Zhiyong; Hou, Sen; Li, Linhao; Jenkins, A. Tobias A.; Fan, Yubo
Abstract: The evolved resistance of antibiotics exhibited by some dreaded clinical pathogens and formation of biofilms has caused life-threatening problems for patients with burns and other wounds. Here, in order to avoid antibiotic overuse, and thus decreasing the occurrence of antimicrobial-resistant bacteria, a theranostic wound dressing, composed of biocompatible UV-photocrosslinkable methacrylated gelatin (GelMA) encapsulating both antimicrobial and fluorescent vesicles, has been developed. The system can respond to the microbiological environment of the wound via a simple color change and antimicrobials release only when require and this is in essence passive as they do not respond to their local environments and benign bacteria, and only operates when pathogenic bacteria exist. Both in Vitro and i n Vivo study demonstrated that the proposed wound dressing was able to kill/inhibit the growth of methicillin-resistant S. aureus and P. aeruginosa, whilst providing a visual warning of infection, due to vesicle bilayer membrane lysed by toxins secreted by the two strains of pathogens but not by a non-pathogenic Escherichia coli species. The strategy of microbiologically responsive wound dressing proposed here could also be used as a general methodology for the design and fabrication of bacterial responsive functional biomaterials that offer opportunities to combat drug-resistant bacterial infections.